Meningkatkan penguasaan kosakata Bahasa Inggris melalui video lagu Nobody’s son - Situmorang, Cici; Ramadhani, Lia Amalia; Fadilah, Iqna Nur; Romadhon, Raffa Fahdiaz (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to measure the extent to which the use of English song videos, particularly “Nobody's Son,” improves students' vocabulary mastery and to identify students' learning strategies when using this medium as a fun and meaningful learning tool. This study uses a qualitative descriptive method with interviews as the main data collection technique. The research subjects consisted of English Education students at the Prima Bangsa Institute in Cirebon, who were selected using purposive sampling. The findings showed a significant shift in motivation, with students feeling more relaxed and enthusiastic due to a decrease in their psychological barriers or “affective filters.” The visual elements in the music video helped students understand the meaning of abstract words through emotional narratives, thereby improving their memory retention. In addition, the use of music videos encourages independent learning outside of class hours and helps students master vocabulary functionally and contextually. The use of the music video “Nobody's Son” effectively improves vocabulary mastery by providing an authentic context and emotional engagement. The audio-visual elements in this media successfully lowered students' affective filters, reduced anxiety, and increased learning motivation. In addition, this media encourages independent learning and helps students shift from passive memorization to active use.